Gram-scale synthesis of the p38α MAPK-inhibitor VX-745 for preclinical studies into Werner syndrome. (September 2010) - Bagley, Mark C; Davis, Terence; Dix, Matthew C; Fusillo, Vincenzo; Pigeaux, Morgane; Rokicki, Michal J; Kipling, David
Background: The ATP-competitive p38α MAPK inhibitor VX-745 exhibits an exquisite kinase selectivity profile, is effective in blocking p38 stress signaling in Werner syndrome dermal fibroblasts, has efficacy in clinical trials and may have therapeutic value against Werner syndrome. Previous synthetic routes, however, have only resulted in milligram quantities suitable for cell-based studies, whereas gram quantities would be required for in vivo use.Results & discussion: Microwave irradiation using a stop–flow monomodal microwave reactor has been found to facilitate scale-up of the synthesis of VX-745. Ullmann-type C–S bond formation using thiophenol, chloropyridazine, copper(I) catalyst and diol ligand proceeds rapidly and efficiently in this apparatus for elaboration to the pyrimido[1, 6- b ]pyridazinone core of VX-745 on gram scale and with good overall yield.Conclusion: This method delivers the p38 inhibitor VX-745 in sufficient quantities for preclinical studies to rescue the aging phenotype in Werner syndrome.